Efisiensi Transaksi Pembayaran Digital Berbasis QRIS pada Warmindo di Sekitar UMS - Ikrar Nusa Bhakti; Yuli Chomsatu Samrotun; Dimas Ilham Nur Rois (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The goal of this research is to look into the benefits, availability, and hazards of using QRIS effectively in Warmindo, near Muhammadiyah University in Surakarta. The research population consists of all QRIS subscribers in Warmindo near the UMS, as well as a random selection of 50 respondents. Data was collected using a random sample strategy and analyzed with multiple linear regression. The results suggest that the benefits and convenience of use of the QRIS improve performance but have no meaningful influence on risk perception. These items will educate merchants and decision-makers on the value of benefits and access to the advancement of digital payment technology.